Sleep Quality Among Employees of Institut Teknologi Sumatera (ITERA), Lampung, Indonesia: A Cross-Sectional Study in Higher Education Using the Pittsburgh Sleep Quality Index (PSQI) - Esra Maduma Sinurat; Gres Maretta; Yanti Ariyanti (Jurnal Penelitian Pendidikan IPA, 2026)
Sleep is a vital physiological process essential for overall health and productivity. Among university employees, poor sleep quality has been linked to reduced job performance, increased risk of mental health disorders, and heightened susceptibility to occupational burnout. These risks are particularly salient in academic environments, where high administrative demands and blurred work-life boundaries are increasingly common. This study evaluated sleep quality among employees at Institut Teknologi Sumatera (ITERA) while investigating key demographic predictors. Employing a cross-sectional quantitative design, data were collected from 300 administrative and academic staff using the Pittsburgh Sleep Quality Index (PSQI). Initially, a chi-square goodness-of-fit test was conducted to assess the associations among categorical variables, and a generalized linear model (GLM) was subsequently utilized to identify factors influencing sleep quality, with a significance threshold of p < 0.05. The results revealed that approximately 75.67% of employees exhibited good sleep quality. Notably, significant sex differences were observed: females demonstrated a higher prevalence of poor sleep quality compared to males. Furthermore, age emerged as a critical predictor, with employees in the 41–50 age group reporting better sleep quality than those in the 21–30 and 31–40 age groups. These findings underscore the importance of considering demographic factors when developing targeted interventions aimed at improving sleep health in organizational settings.